Performance analysis and emission characteristics of VCR diesel engine fuelled with algae biodiesel blends. (2021) - Prabakaran, S.; Manimaran, R.; Mohanraj, T.; Ravikumar, M.
Abstract: In the present work, algae-biodiesel was prepared through the transesterification process. Subsequently, the thermophysical properties of algae-biodiesel (B100) and algae-biodiesel blends (B10, B20) were tested by ASTM standards. Finally, the Performance and exhaust emission parameter analysis was investigated for algae-biodiesel blends (B10, B20) compared with neat diesel results for a variable compression ratio (CR) of CR17 and CR18 on Kirloskar single-cylinder compression ignition engine. Among those in the different blends evaluated, algae-biodiesel blend (B20) at CR18 provide a closer approximation of the effects of diesel in better brake thermal efficiency, lower carbon monoxide (CO) and hydrocarbon (HC) emissions along with oxides of nitrogen (NOx ) found to be slightly higher.